11th EAD Conference Proceedings: The Value of Design Research 2016
DOI: 10.7190/ead/2015/139
|View full text |Cite
|
Sign up to set email alerts
|

The design ideation process of character animation story

Abstract: The design ideation process of a character animation story was researched in this study. The critical design ideation process of experts' thinking was normalized. The Design Structure Matrix approach was used to analyze the ten basic elements which influences story ideation and to find the correlation between design elements regarding their independence, dependence and interaction in two senior animation experts' design ideation process. Then the experts' complex thinking was analyzed. The results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Contemplating ideas is associated with the ability of reasoning, self-reflection, of the ability to acquire, apply intellect, intuition and inspiration, etc. In Wu et al [8] analysis of ideas are identified by three different types of ideas : new , revised and modified. The idea that team discussed it for the first time in the ideation session is called new idea.…”
Section: Analysis Type N Analysis Tool Linkograph Matrix Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Contemplating ideas is associated with the ability of reasoning, self-reflection, of the ability to acquire, apply intellect, intuition and inspiration, etc. In Wu et al [8] analysis of ideas are identified by three different types of ideas : new , revised and modified. The idea that team discussed it for the first time in the ideation session is called new idea.…”
Section: Analysis Type N Analysis Tool Linkograph Matrix Referencesmentioning
confidence: 99%
“…The 'cluster size' is the number of ideas in the cluster. For further details, we refers to this research work; Bilda and Gero [14] and In Wu and al [8].…”
Section: Analysis Type N Analysis Tool Linkograph Matrix Referencesmentioning
confidence: 99%
See 1 more Smart Citation